Precision Irrigation in Agriculture Using an IoT Based Smart Water Management Platform: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2021)
Water is available for something like the  world's public's energy security, with agribusiness  accounted for 70% of river use. Leaks in transit and land  management, while also suitable processing practices, are  the leading causes of water losses and vegetable production.  Irrigation for agriculture is the world's largest user of  freshwater, arguing for the widespread application use of  data to improve plant health, reduce energy use, and  calibrate water usage Even if the Digital revolution (IoT)  and also other telecommunication technologies seem like a  natural match for smart - grid components, its viability must  be included in real-world circumstances via the use of on site pilots. In addition, Home automation software testing  games should be adaptable to a wide range of crops,  growing conditions, and countries. SWAMP is a project  that develops and tests IoT-based smart energy  management methods and technologies for precision  farming in Europe, Belgium, and Latin America. We go  through the project's SWAMP viewpoint, townscape, crew  members, and statistics ways to do things. In this article.
Keywords: Agriculture; Internet of Things; Precision Irrigation; Smart Water Management